Study on cation exchange of a lead coordination polymer targeting dynamic mixed cation doped and mixed-valent coordination polymers / Hamisu Aliyu Mohammed - Hamisu Aliyu , Mohammed (2020)
Solid solution in Metal-Organic Coordination Polymers (MOCPs) is an emerging synthetic pathway for modifying chemical compositions and has been expansively investigated. It has been demonstrated to be an important tool for engineering novel functional materials that otherwise have not been synthesized via the conventional technique. Although stable solid material with variable functionalities and intriguing structural motifs could be engineered by judicious selection of multivariate metal centers and multifunctional ligands. However, solid solution featuring mixed valence in MOCP is rare. Motivated by the ability of Pb2+ to adopt range of coordination numbers (CN) and chemical environments (CE), in addition to its flexibility to readily undergo cation exchange owing to its low electronegativity, we opted for solid solution in Pb-based MOCP. Herein, we exploited a dynamic 3D, Pb-based MOCPs that contain 1D moiety featuring 3 distinctive Pb2+ sites each with different CN and CE that can potentially undergo cation exchange with exogenous divalent and aliovalent including mono- or trivalent cations. Under optimized condition, we achieved to our knowledge the first, hetero-valent, single and multiple valent substituted MOCP featuring cation vacancy. In addition to this, under the guidance of Pearson’s Hard-Soft Acid-Base (HSAB) principle, we gained the control of the process and tune the % of cations exchange under appropriate conditions. A tunable photoluminescent (PL) emission exhibiting good antenna effect and retention of the original 3D MOCP was observed when doped with as little as 6 wt% of Eu3+. Remarkably, the PL intensity of the Eu3+ substituted MOCP increases as the amount of Eu3+ increases even up to 80 wt. %, which is also a rather rare case and the first, to the best of our knowledge in MOCP solid solution. 10 wt. % Eu3+ substituted MOCP was found to have a significant conductivity improvement at 25 oC. Fe2+ substituted MOCP was also found to have some magnetic hysteresis at room temperature, another very rare case of mononuclear or cluster Fe2+ doped to show some hysteresis at RT. The formation of solid solution and phase purity of these compounds were confirmed by single crystal and powder X-ray diffractions, SEM-EDX, ICP-OES as well as XPS.